EVALUATION OF LACTICIN ADDITION ON GAS PRODUCTION KINETICS AND RUMEN METHANOGENESIS in Vitro - Jayanegara, A.; Makkar, H.P.S.; Becker, K. (Diponegoro University, 2014)
The present study was aimed to investigate the effect of a novel bacteriocin, i.e. lacticin 3147, ongas production kinetics and methane emission under in vitro rumen environment in two consecutiveexperiments. In experiment 1, either no or 10 µM of lacticin was added to hay or hay:concentrate (1:1,w/w) substrate. In experiment 2, the levels of lacticin additions were extended to 0, 10, 25 and 50 µM.Samples were incubated in three replicates in both experiments at 39oC for 24 h. Total gas productionand methane emission were measured during and after the incubation, respectively. Results revealedthat, in general, addition of lacticin had limited significant effects on gas production parameterscompared to control (without lacticin addition). Lacticin addition up to 50 µM did not significantlydecrease CH4 emission, although a tendency of methane reduction existed when lacticin was added at 25µM. Hay diet produced significantly less methane emission than that of hay:concentrate diet both inexperiment 1 and experiment 2 (P<0.05). It can be concluded that lacticin addition up to 50 µM wasunable to decrease CH4 emission in vitro and therefore need to be tested further at higher concentrations.